Services Trade and Development : The Experience of Zambia - Mattoo, Aaditya; Payton, Lucy (Washington, DC: World Bank and Palgrave Macmillan, 2012)
Some see trade in services as irrelevant to the development agenda for least developed countries (LDCs). Others see few benefits from past market openings by LDCs. This book debunks both views. It finds that serious imperfections in Zambia's reform of services trade deprived the country of significant benefits and diminished faith in liberalization.